Designing nanomolar antagonists of DC-SIGN-mediated HIV infection: ligand presentation using molecular rods1. Issue 18 (4th March 2015) - Ordanini, Stefania; Varga, Norbert; Porkolab, Vanessa; Thépaut, Michel; Belvisi, Laura; Bertaglia, Andrea; Palmioli, Alessandro; Berzi, Angela; Trabattoni, Daria; Clerici, Mario; Fieschi, Franck; Bernardi, Anna
<x xml:space="preserve">Abstract</x> Rational design of DC-SIGN antagonists combines a selective glycomimetic ligand with trivalent dendrons spaced by a rigid core and allows to exploit multiple multivalency effects.